Estetyka afektu. Video-art Billa Violi - Taczkowska, Kalina (Hybris, 2021)
The aim of the thesis is to discuss selected Bill Viola’s pieces characterized by their high affective content in order to get insight into video-art as an artistic genre. The author claims that what distinguishes video art from other forms of art is its affective potential.